Taxonomic notes in Microlicia (Melastomataceae, Microlicieae) - Romero, Rosana (Phytotaxa, 2013)
The genus Microlicia comprises approximately 130 species, the characters that define the species are very often tenuous, making delimitation between closely related species difficult. As a result of a taxonomic study on Microlicia, 14 new synonyms are proposed here and 10 lectotypes are designated.